Teachers’ and Students’ Experiences in Utilizing Smart Classroom for the Development of GuideTech: A Technological Guide for Smart Classroom Utilization - CAPUNITAN, APRIL JOY; FELICIANO, DIVINA (International Journal of Arts, Sciences and Education, 2025)
This study aims to explore the experiences of teachers and students in using smart classrooms for teaching and learning through a Focus Group Discussion. The findings serve as the foundation for developing GabayTek: A Technology Guide for Smart Classroom Utilization, a supplementary material for educators and learners. The study revealed that teachers and students had varying experiences with smart classrooms. While some encountered difficulties in using the technology, they remained optimistic about its potential to enhance efficient and widespread learning. Teachers affirmed that smart classrooms fostered more interactive and systematic lessons, increasing student engagement. However, they faced challenges such as a lack of training, limited access to learning resources, and technical issues. On the students' side, digital tools made learning more accessible, yet some struggled with platforms like Google Forms and cloud computing. Additionally, prolonged screen exposure caused physical strain for some learners. Thorough evaluation and validation confirmed that GabayTek meets high academic and pedagogical standards. Users provided positive feedback, highlighting its well-structured content, effective design, and usefulness in simplifying learning. Teachers welcomed GabayTek as a valuable educational tool, reinforcing its efficiency in teaching and learning. The study recommends continuous training for teachers and the refinement of language guidelines for digital platforms. This will maximize the benefits of smart classroom technology in education, ensuring more effective and inclusive learning experiences.